1990
DOI: 10.1038/346390a0
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana contains two genes for TFIID

Abstract: The general transcription initiation factor TFIID plays a primary part in the activation of eukaryotic genes transcribed by RNA polymerase II. Binding of TFIID to the TATA box initiates the assembly of other general transcription factors as well as RNA polymerase II at the promoter resulting in a preinitiation complex capable of accurate transcription initiation in vitro. Human TFIID has been shown to interact with various regulatory factors. The observation that stimulation of transcription by different trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 30 publications
5
90
0
Order By: Relevance
“…[29][30][31] Using low-stringency hybridization, 2 distinct TBPs were identified in Arabidopsis thaliana and then in maize. 43,44 Since then, 3 TBP-related factors (TRFs; TRF1, TRF2 and TRF3) have been discovered in the animal kingdom based on their homology to the C-terminal core domain of TBP (for a review see refs. [45][46][47][48][49].…”
Section: Tbp-related Factorsmentioning
confidence: 99%
“…[29][30][31] Using low-stringency hybridization, 2 distinct TBPs were identified in Arabidopsis thaliana and then in maize. 43,44 Since then, 3 TBP-related factors (TRFs; TRF1, TRF2 and TRF3) have been discovered in the animal kingdom based on their homology to the C-terminal core domain of TBP (for a review see refs. [45][46][47][48][49].…”
Section: Tbp-related Factorsmentioning
confidence: 99%
“…Both factors are able to confer basal transcription but exhibit a different binding pattern in electrophoretic mobility shift assays [25]. We report here the isolation and characterization of two different types of cDNA clones from a maize leaf cDNA library encoding TATA box binding proteins.…”
mentioning
confidence: 98%
“…The proteins derived from the longest open reading frames of the different cDNAs reveal the highly conserved structural motifs common to the C-terminal region of TFIID and display a N-terminal domain which is different from the TFIID clones of other organisms analysed so far. A maize leaf cDNA library in lambda ZAP (Stratagene) was screened with u 538 bp HindlI/EcoRI fragment of the TFIID cDNA AT1 from Arubidopsis rhuhrta [25] by standard procedures [26]. Hybridization with the DIG-labeled probes (Boehringer) was performed at 42°C for at least I6 h in a buffer containing 5x SW, 20% fonnamide, 0.1% sarcosyl, 0.02% SDS and 2% blocking powder (Boehringer) followed by washes at 65°C for 15 min each in 2x SW, 0.1% SDS and 0.…”
mentioning
confidence: 99%
“…Actually, the affinity between TBP and TATA-box DNA is known to be very high (Kd = 2 -4 x 10-9 M) (41). Alternatively, TBP may utilize the helixloop-helix (HLH) motif kown as a structure for protein-protein interaction, since TBP is thought to contain a HLH motif in the C-terminal domain (40 (24,25).…”
Section: Multinerization Of Tbp In Solutionmentioning
confidence: 99%
“…We found that the C-terminus of TBP was essential for TBP-TBP interaction. The C-terminal domain of TBP has multiple motifs/domains for DNA binding (basic repeat, direct repeat and sigma homology) (38)(39)(40). X-ray crystallography has shown that TBP forms a saddle shape structure (23).…”
Section: Multinerization Of Tbp In Solutionmentioning
confidence: 99%